1991
DOI: 10.1016/0002-9610(91)90590-a
|View full text |Cite
|
Sign up to set email alerts
|

Emergency laparoscopy

Abstract: Unnecessary abdominal explorations in severely injured patients can be reduced by employing emergent or urgent laparoscopy in blunt abdominal trauma and the obscured, acute abdominal cases. In 150 blunt abdominal trauma cases, a mini-laparoscopy was used in the emergency room or the intensive care unit without major complications. In 56%, the findings were negative. In 19%, the laparoscopic findings were corroborated by surgery. In 25%, a minimal to moderate hemoperitoneum was found and the laparoscopic impres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 7 publications
0
38
0
3
Order By: Relevance
“…Such limitations were also described by LIVINGSTON et al (1992) andIVATURY et al (1993). According to BERCI et al (1991), the visualization of some areas can be realized through placement of a second trocart. GOMEL (1976);NAGY &JAMES (1989) andGOMES (1993) described the laparoscopy technique as a secure and succesfull method in the visualization of the intracavitary structures.…”
Section: Discussionmentioning
confidence: 99%
“…Such limitations were also described by LIVINGSTON et al (1992) andIVATURY et al (1993). According to BERCI et al (1991), the visualization of some areas can be realized through placement of a second trocart. GOMEL (1976);NAGY &JAMES (1989) andGOMES (1993) described the laparoscopy technique as a secure and succesfull method in the visualization of the intracavitary structures.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies throughout the 1970s and 1980s proved laparoscopy effective in detecting intraabdominal injuries [74,75,76,77,78]. These studies suggest laparoscopy may serve a role in establishing diagnosis in abdominal trauma cases where peritoneal lavage has not been definitive.…”
Section: Laparoscopic Approach To Splenic Cysts Aneurysms and Traumamentioning
confidence: 98%
“…Since then, Gazzaniga et al 5 noted that laparoscopy is useful for determining the need for laparotomy. In 1991, Berci et al 6 reported that he had reduced the number of nontherapeutic laparotomy performed for hemoperitoneum by 25% through the use of laparoscopy in 150 patients with blunt abdominal trauma. Chol et al reported reduced negative and nontherapeutic laparotomy rates in this identified population.…”
Section: Introductionmentioning
confidence: 99%